THE ASSOCIATION OF OXIDATIVE STRESS STATUS AND GLAUCOMA: SYSTEMATIC REVIEW - Amalia Swastika, Widya (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
At this point in time, we do not have a full understanding of the pathogenic processes that might lead to glaucoma. Other concurrent variables, such as elevated glutamate levels, changes in nutritional status, abnormalities in vascular parameters, malfunction of the immune system, and oxidative stress, may also play key roles in the genesis and pathophysiology of the condition. However, the levels of antioxidant enzymes such as superoxide dismutase (SOD), glutathione peroxidase (GPX), and catalase (CAT) were found to be enhanced in the aqueous humors of the open-angle glaucoma (OAG) group. The outcomes of the study indicated that the blood TAS was lower in the OAG group than in the control group. OAG is a complicated illness, and a number of different variables, including age, genetics, inflammation, and oxidative stress, have the potential to all play a role in its progression. In individuals who have priamry open-angle glaucoma (POAG), however, damage to the optic nerve and loss of vision can result from intraocular pressure readings that are within the normal range. One of the most important variables that might lead to POAG is having an intraocular pressure that is too high. It would indicate that oxidative stress plays a part in the evolution of glaucomatous optic nerve damage; nonetheless, the causes of open angle glaucoma are still a mystery. The age-related disorder known as exfoliation glaucoma (EXG) is the factor responsible for secondary OAG the majority of the time. The abnormal synthesis and deposition of extracellular fibrillar material are the defining characteristics of this condition. Although the specific processes that underlie the development of exfoliative syndrome and the subsequent transition from exfoliative syndrome to EXG remain unknown, it has been shown that exfoliative syndrome can lead to EXG.